KENDALA PELESTARIAN OLAHRAGA MASYARAKAT SEBAGAI MATERIAL CULTURE PADA GENERASI MUDA PERKOTAAN: A GROUNDED RESEARCH - Abd. Rahman Azahari (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
Abd. Rahman Azahari   This study describes constraints affecting social sport as material culture received minor perception for young generation and the sport is left in modern information technology.  This study used grounded research emphasizing an indepth data analysis to achieve wise phenomenon.  Data were collected using participatory observation and indepth interviews.  Two traditional Dayak sports in Central Kalimantan were observed:  menyipet (to blow with a pipe) and balago in January to July 2015, involving sport organization heads, cultural heads, sport teachers, coaches, and athletes as informants.  Data were analyzed using open coding, axial coding and selective coding from Strauss and Corbin.  The study revealed: (1) internal problems include: monotonous rules of the games, no more funs, hard to train, and do not serve to earn money; (2)  external problems include:  lack of coordination between government offices, limited invitation games,  complex government regulation and policy, restricted facilities for traditional sports.